Integration of ‘Mindfulness’ into preschool practices : way to enhance children’s and educator’s well-being - Helen Rose Philip 1982- (2022)
In early childhood, the provision of a positive and warm environment, interactions, experiences, and where children´s well-being is enhanced are the conditions that support the development of their social and emotional skills. Preschools are considered the first school level in the education system in Iceland and play a vital role in young children's lives. The National Curriculum Guide emphasizes that schools should create a positive school culture that enhances children's health and well-being. Further, educators place a vital role in children's social, emotional, and cognitive development. Supporting educators’ well-being will positively impact children's well–being. International research shows that mindfulness training can enhance social and emotional skills and well–being in children and educators. Although Icelandic schools have started to implement mindfulness, there are not many studies about the impact of mindfulness in schools. The aim of this qualitative research was to investigate how one preschool in the capital area integrated mindfulness into preschool practices. Further, the present study explored the educators' views on the influence of mindfulness on children's and educators' well-being. The research questions guiding this study are; 1. How can mindfulness be integrated into preschool practice? 2. How do preschool educators express their views towards the influence of mindfulness on children's and educators' well-being? The data was collected primarily using observation, research diary, video stimulation accounts, and interview methods. The study participants consisted of four educators and twenty children (video purpose only) from a preschool. The study results indicate that for effective integration of mindfulness into preschool practices, first, needs to integrate mindfulness among educators. Once the educators have acquired the mindfulness skills, the next step is integrating mindfulness among children. Further, according to the educator's view, the study results indicate that mindfulness ...